2013
DOI: 10.15389/agrobiology.2013.1.68eng
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Intermediary Wheat-Agropyron Hybrids on Resistance to Leaf Rust

Abstract: S u m m a r yThe estimation was made for 18 variants of octaploid winter wheat-Аgropyron hybrids (WAH) (2n = 56) on juvenile resistance to 10 isolates of leaf rust. By the use of molecular markers the presence of different subgenomes of Thinopyrum sp. in investigated variants was shown. In variants of WAH the authors revealed a polymorphism on resistance to test-isolates of leaf rust, which may be due to various number of agropyron chromosomes in genome. The authors discussed the possibility of using studied W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…The results of the in situ hybridization experiments showed that four studied WWGHs differ in the composition of wheatgrass chromosomes and, accordingly, are potential sources of different genes of agronomically valuable traits for introgression in wheat genome. Indeed, in our previous studies, as well as in the breeder estimations, the studied WWGHs accessions demonstrated the differences in bread-making quality, post-harvest regrowth, perenniality, seed storage proteins composition, resistance to leaf rust, salt tolerance, resistance to pre-harvest sprouting, and other traits [ 25 , 26 , 54 , 55 , 56 ]. Additionally, molecular studies demonstrated that the four studied WWGHs has different allelic state of the wheatgrass genes that are associated with the studied traits [ 26 , 55 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of the in situ hybridization experiments showed that four studied WWGHs differ in the composition of wheatgrass chromosomes and, accordingly, are potential sources of different genes of agronomically valuable traits for introgression in wheat genome. Indeed, in our previous studies, as well as in the breeder estimations, the studied WWGHs accessions demonstrated the differences in bread-making quality, post-harvest regrowth, perenniality, seed storage proteins composition, resistance to leaf rust, salt tolerance, resistance to pre-harvest sprouting, and other traits [ 25 , 26 , 54 , 55 , 56 ]. Additionally, molecular studies demonstrated that the four studied WWGHs has different allelic state of the wheatgrass genes that are associated with the studied traits [ 26 , 55 ].…”
Section: Discussionmentioning
confidence: 98%
“…WWGHs carry a combination of wheat and wheatgrass genomes, which makes it possible to use them as breeding bridges to facilitate the transfer of genes of interest from wheatgrass to wheat [ 18 , 19 , 20 , 21 , 22 , 23 ]. Many partial WWGHs possess unique composition of wheatgrass chromosomes associated with agronomically valuable traits [ 24 , 25 , 26 , 27 ]. They have good baking qualities, are resistance to leaf rust, drought, and salinization.…”
Section: Introductionmentioning
confidence: 99%
“…They carry valuable genes of resistance to salinity, drought and low temperatures [31,32], as well as to pre-harvest sprouting [33]. Forms of wheat with the genetic material of wheatgrass have been developed, which have resistance to leaf rust [34][35][36], stem rust [37], fusariosis [38], wheat streak mosaic virus [39] and other diseases. Chromosomes of rush and intermediate wheatgrass are relatively easy to conjugate and exchange patches [40].…”
Section: Introductionmentioning
confidence: 99%
“…С использованием муки тритикале изготовляют макаронные изделия, печенье, бисквиты, крекеры, диетический хлеб для людей, страдающих нарушением обмена веществ. Одним из способов улучшения хлебопекарных качеств тритикале считается замещение хромосомы 1R ржи на гомеологичную хромосому 1D пшеницы (12). Потенциальный интерес для улучшения хлебопекарных качеств тритикале представляет также замещение хромосомы 1R ржи на хромосому 1U Aegilops umbellulata (13).…”
unclassified